2023
DOI: 10.3390/life13061345
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Trends in the Prevalence of Markers for Hepatitis E Virus Exposure in the Heterogeneous Bulgarian Population

Abstract: The prevalence of hepatitis E virus (HEV) in the Bulgarian population remains underestimated. The aim of the present study was to evaluate age and gender trends in HEV prevalence in the heterogeneous Bulgarian population. Stored serum samples from blood donors and different patient sub-populations—kidney recipients (KR), patients with Guillain–Barre syndrome (GBS), Lyme disease (LD), patients with liver involvement and a clinical diagnosis other than viral hepatitis A and E (non-AE), hemodialysis (HD) and HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…Dogs and cats are carnivores and it is possible that they can become infected via the food chain by consuming raw meat contaminated with swine HEV gt 3 or rat HEV-C1. Furthermore, the moderate HEV seropositivity in our dogs (21.1%) and cats (17.7%) is similar to that found among Bulgarian blood donors (25.9%) [20] and individuals with Guillain-Barre syndrome (24.5%) [61].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Dogs and cats are carnivores and it is possible that they can become infected via the food chain by consuming raw meat contaminated with swine HEV gt 3 or rat HEV-C1. Furthermore, the moderate HEV seropositivity in our dogs (21.1%) and cats (17.7%) is similar to that found among Bulgarian blood donors (25.9%) [20] and individuals with Guillain-Barre syndrome (24.5%) [61].…”
Section: Discussionsupporting
confidence: 85%
“…Both previous Bulgarian studies [ 33 , 34 , 35 , 36 , 37 , 44 , 50 ] and the current results of this research show that HEV infection is widespread among animals in our country. Furthermore, HEV seropositivity is widespread among some groups of the Bulgarian population: blood donors (25.9%) [ 20 ], general hunters (48.7%) [ 20 ], hunters of wild boars (51.6%) [ 20 ], and individuals with Guillain-Barre syndrome (24.5%) [ 61 ]. These facts are a serious reason for increasing surveillance and control of HEV infection among animals and humans in Bulgaria.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found a significant proportional excess of male HEV RNA-positive donors compared with the total donor population in our data that exceeded the usual bias of a male surplus in blood donation. Interestingly, a study in Bulgaria showed that although the prevalence of past HEV infections (IgG-positive, IgM-negative, HEV RNA-negative) was similar in males and females, the prevalence of recent or ongoing infection (IgM- or HEV RNA-positive) was twice as high in men [ 30 ]. Future studies on the course of seroconversion in males and females may provide deeper insights into this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…However, the age-prevalence relationship for HEV infection can vary across settings. Factors such as local transmission dynamics, variations in sanitation practices, animal reservoirs, and changing demographics can all influence the age distribution of HEV infection in different ways ( Golkocheva-Markova et al, 2023 ). Thus, it’s important to consider the specific context of each study and population when interpreting the relationship between age and HEV infection.…”
Section: Discussionmentioning
confidence: 99%